C1-Almost Periodic Solutions of BAM Neural Networks with Time-Varying Delays on Time Scales - Yongkun Li; Lili Zhao; Li Yang (The Scientific World Journal)
On a new type of almost periodic time scales, a class of BAM neural networks is considered. By employing a fixed point theorem and differential inequality techniques, some sufficient conditions ensuring the existence and global exponential stability of C1-almost periodic solutions for this class of networks with time-varying delays are established. Two examples are given to show the effectiveness of the proposed method and results.